2019
DOI: 10.3389/fmicb.2019.01782
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Gene Expression in Ducks Infected With Waterfowl-Origin H5N6 Highly Pathogenic Avian Influenza Viruses

Abstract: Clade 2.3.4.4 H5 avian influenza viruses (AIVs) are widely prevalent and of significant concern to the poultry industry and public health in China. Nowadays, the clade 2.3.4.4 H5N6 virus has become a dominant AIV subtype among domestic ducks in southern China. We found that waterfowl-origin clade 2.3.4.4 H5N6 viruses (A/goose/Guangdong/16568/2016, GS16568 and A/duck/Guangdong/16873/2016, DK16873) isolated from southern China in 2016 could replicate in multiple organs of inoculated ducks. DK16873 virus caused m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Ducks infected with HPAI H5N1 strains A/goose/Guangdong/16568/2016 (GS16568), and A/duck/Guangdong/16873/2016 (DK16873) showed sustained responses of type I IFNs post infection. However, the time points used in these experiments were 12 HPI and 2 DPI (Wu et al, 2019). While these highly pathogenic strains of flu could be eliciting sustained responses, other strains of H5N1 had the peak of IFN upregulation at 1 DPI (Saito et al, 2018).…”
Section: Type I Ifnsmentioning
confidence: 99%
“…Ducks infected with HPAI H5N1 strains A/goose/Guangdong/16568/2016 (GS16568), and A/duck/Guangdong/16873/2016 (DK16873) showed sustained responses of type I IFNs post infection. However, the time points used in these experiments were 12 HPI and 2 DPI (Wu et al, 2019). While these highly pathogenic strains of flu could be eliciting sustained responses, other strains of H5N1 had the peak of IFN upregulation at 1 DPI (Saito et al, 2018).…”
Section: Type I Ifnsmentioning
confidence: 99%
“…After infection with HPAIVs, such as H5N1 and H7N1, waterfowl develop a limited inflammatory response, usually with little or no mortality, but chickens display a rapid and strong inflammatory response and the infection can induce severe disease symptoms (Bean et al, 2013;Cornelissen et al, 2013;Burggraaf et al, 2014). Innate-immune related genes were involved in the chickens and ducks innate immune response to H5N6 HPAIVs infection (Gao et al, 2017;Wu et al, 2019), but the difference in the inflammatory response to H5N6 between chickens and ducks and the pathogenic relevance of cytokine are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our previous studies suggested that chicken-origin and goose-origin H5N6 HPAIVs isolated from Southern China in 2016 exhibited high pathogenicity in chickens [51]. In addition, duck-origin and goose-origin H5N6 HPAIVs were also able to kill ducks [52]. Therefore, these results suggested that clade 2.3.4.4 H5N6 HPAIVs isolated from Southern China in 2016 have become a huge threat to poultry industry.…”
Section: Discussionmentioning
confidence: 88%